The known, unknown, and the intriguing about members of a critically endangered traditional medicinal plant genus Aconitum - Kakkar, Richa Ashok; Haneen, Mariam Azeezuddin; Parida, Akash Chandra; Sharma, Gaurav (Frontiers in Plant Science, 2023)
Humanity will always be indebted to plants. In the ongoing scientific era, the ‘Herbal Revolution’ has helped discover several valuable medicinal plants and associated novel secondary metabolites from the diverse unexplored ecosystems, treating several diseases via phytotherapy. The Aconitum genus comprises several economically-important poisonous mountainous medicinal plant species whose unique biodiversity is on the verge of extinction due to illegal human intervention triggered habitat loss, over-harvesting, and unrestricted trading. Owing to its vast diversity of diterpene alkaloids, most species are extensively used to treat several ailments in rural parts of the world. Irrespective of this, many unexplored and intriguing prospects exist to understand and utilize this critical plant for human benefit. This systematic review tries to fill this gap by compiling information from the sporadically available literature known for ~300 Aconitum spp. regarding its nomenclature and classification, endangerment, plant morphology, ploidy, secondary metabolites, drug pharmacokinetics, conservation, and omics-based computational studies. We also depicted the disparity in the studied model organisms for this diverse genus. The absence of genomic/metagenomic studies is becoming a limiting factor in understanding plant physiology, metabolic pathways, and plant-microbes interactions, and therefore must be promoted. Additionally, government support and public participation are crucial in establishing conservation protocols to save this plant from endangerment.